TEKNIK STRUCTURED NUMBERED HEADS UNTUK PEMBELAJARAN KETERAMPILAN MEMBACA BAHASA JERMAN PESERTA DIDIK SMAN 1 KUTOREJO KELAS XI SEMESTER 1 - WIJIARTI, ANJAR (LATERNE, 2018)
The main purpose of this study represents the difficulties of students? skill in reading German language. Based on the results of research Wardati 2015 indicated that 67% the senior high school students do not understand in reading and understanding german language. The technique of Structured Numbered Heads was applied in this study as an alternative learning technique for German reading skill. This technique is very well when its applying while learning german language because it can reduce the boredom of learners and not only develop the cognitive abilities but also train the learners to be responsible. This research was applied to students of XI IPS 2 semester 1 in SMAN 1 Kutorejo with the theme of family. The research data is in the form of tests and questionnaires. The results showed that the test and the learners response to the stimulus given in the German reading skills with the Structured Numbered Heads technique went well. This is evidenced by the increase in the average value of learners after SNH technique applied. By looking at the results of the test and questionnaire learners can be concluded that the response of learners in learning German language skills with SNH technique is good. This is evidenced by the results of the test results to-1 with an average of 65, the second meeting with an average value of 92.2 and 3rd meeting with an average value of 97.8 and the results of questionnaires with an average of 67, 5%. Keyword : The technique of Structured Numbered Heads, Response, German language